Modulating interfacial polymerization with phytate as aqueous-phase additive for highly-permselective nanofiltration membranes - Zhang, Miaomiao; You, Xinda; Xiao, Ke; Yin, Zhuoyu; Yuan, Jinqiu; Zhao, Junhui; Yang, Chao; Zhang, Runnan; Wu, Hong; Jiang, Zhongyi (Journal of membrane science, 2022)
Modulating interfacial polymerization (IP) process has been recognized as an effective way to optimize the physicochemical structure of polyamide membranes and thus elevating nanofiltration performance. Herein, phytic acid dodecasodium salt (PADS), a small molecule salt with high solubility, is used as an aqueous-phase additive to modulate the piperazine (PIP) monomers diffusion behavior via electrostatic interaction during the IP process. The PADS with a high charge density can form long-range electrostatic interaction with the PIP molecules to retard their diffusion. The diffusion coefficient of PIP can be effectively modulated within an order of magnitude (∼10−5-10−6 cm2 s−1) by varying the amount of PADS. Accordingly, the growth of polyamide layer is inhibited and the membrane thickness is reduced from 95 nm to 50 nm. The optimized membrane presents a two-fold increase in water permeance while maintaining excellent salt rejection performance (Na2SO4 rejection >97%), outperforming the benchmark commercial nanofiltration membranes. [Display omitted] •Phytic acid dodecasodium salt (PADS) as additive to modulate interfacial polymerization.•PADS can retard the diffusion of amine monomers by electrostatic interaction.•The thickness of PA membrane is significantly reduced.•The optimized polyamide membrane shows high water permeance and Na2SO4 rejection.